Kolaborasi Pendekatan Pembelajaran Matematika Problem Solving, Pendekatan Pembelajaran Matematika Realistik dan Pendekatan Pembelajaran Matematika Open-Ended - Mutijah Mutjah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Every approach to mathematics learning must have specific characteristics. Problem solving mathematics learning Approached has specific characteristics that issue or question presented must have more than one way to get a correct answer. to Realistic mathematics learning approached (PMR, Ina red) or often called Realistic Mathematics Education (RME) has the characteristic that the learning of mathematics students are taken in the direction that is close to everyday life. Open-Ended Mathematical Learning approached has characteristic that in learning math presented problems required an open issue. The results of a literature review of the three approaches of mathematics learning at the elementary school (SD) can be applied the collaboration between problem solving mathematics learning approached and realistic mathematics approached. Collaboration between realistic mathematical approached and Open-Ended mathematics approached can also be applied. However, based on the specific characteristics of problem solving mathematics learning approached and openended mathematics learning approached so they both can not be collaborated. Among the three approaches of mathematics learning, the more flexible approach to be collaborated is realistic mathematics learning aproached. Keywords: Problem Solving Mathematical Learning Approached, Realistic Mathematics Learning Approached, Open-Ended Mathematics Learning Approached, Collaboration